Inconsistencies and Composition, and the Value Relevance of Non-GAAP Earnings of Red Chip Companies - Rahman, A (American Accounting Association (AAA), 2016)
We examine the relevance of non-GAAP earnings (NGE) reporting in annual reports in a less regulated and less intense information environment, the environment of Red Chip companies of the Hong Kong Stock Exchange (HKSE). It also examines the relevance of reporting and measurement inconsistencies, and composition. Red Chip companies are mainland China companies that are controlled directly or indirectly by the Chinese government and listed in the HKSE. NGE are additional disclosures, and Red Chip companies are primarily listed in the HKSE to seek foreign investment. We find that adjusted results and EBITDA are common forms of NGE reporting, and tax, interest/financial cost, and gain/loss on investment are the main adjustment items used to derive NGE, not all firms make identical adjustments across years and there are variations in reporting across firms. GAAP earnings (GE) rather than NGE are value relevant. Adjustment inconsistencies influence the value relevance of reported NGE.
Keywords: Non-GAAP earnings (NGE); GAAP earnings (GE); Relevance; Reporting inconsistencies; Adjustments inconsistencies